Faktor-Faktor yang Berhubungan dengan Persepsi Remaja Tentang Lesbian, Gay, Biseksual, dan Transgender (LGBT) di SMP Negeri 24 Padang - Febrina Febrina; Waldatul Hamidah (NAJ Nursing Applied Journal, 2025)
Based on the HIV/AIDS information system report of the West Sumatra provincial office, it was stated that Padang City with the number of AIDS cases reported in 2021 recorded 280 people infected with HIV from January to November 2023. The Padang City Health Office stated that the dominant cause with the highest risk of residents infected with HIV AIDS was men who have sex with men (MSM), there was one case of MSM at SMP Negeri 24 Padang. The purpose of this study was to determine the factors related to adolescent perceptions of LGBT at SMP Negeri Padang in 2024.This type of research is "analytical" with a cross-sectional design. This research was conducted in June - September 2024 at SMP Negeri 24 Padang. The population of this study was all students of class VIII of SMP Negeri 24 Padang. The sampling technique was simple random sampling. Data collection used primary and secondary data. Univariate analysis used descriptive statistics and bivariate analysis used the chi square test.The results of the study showed from the chi square test results (p>0.05) there was a significant relationship between adolescent knowledge (p-value = 0.011) and adolescent perceptions about LGBT and there was no significant relationship between adolescent attitudes (p-value = 0.191) and adolescent environment (p-value = 0.802) with adolescent perceptions about LGBT.It was concluded that there was still a lack of adolescent knowledge about LGBT. It is hoped that the results of this study can further increase adolescent knowledge, especially about the dangers of LGBT in reducing the number of HIV transmissions.